An innovative approach in the treatment of trigeminal trophic syndrome. (19th May 2022) - Pisano, Catherine; Fox, Matthew; Reichenberg, Jason
Abstract: Background: Trigeminal trophic syndrome (TTS) is a rare disorder that presents as ulceration of the nasal ala, and less often ipsilateral cheek, cutaneous lip, and forehead, following damage to the trigeminal nerve. TTS is often very difficult to treat due to anesthesia and paresthesia along the distribution of the trigeminal nerve, which often leads to a large behavioral component of this disease. Methods: In this single case report, a thermoplastic mask was sutured in place overlying the chronic ulcerations of TTS in a 57-year-old man. Results: Significant re-epithelization of the chronic ulcerations of TTS was seen after only 6 weeks of thermoplastic mask attachment. Conclusion: While TTS is a chronic and difficult to treat disease, the use of a thermoplastic mask in the treatment of this disease can significantly decrease the self-manipulation component and allow for re-epithelization and healing of the chronic ulcerations.